PROGNOSTIC ROLE OF MOLECULAR SUBTYPES OF COLON CANCER. A CURRENT VIEW ON THE PROBLEM - L. E. Sinyansky; S. V. Vtorushin; S. V. Patalyak; S. G. Afanasyev (Сибирский онкологический журнал)
Purpose of the study: to review the available data on the heterogeneity of colon cancer and to assess the prognostic significance of colon cancer subtypes.Material and Methods. Medline, PubMed, Cochrane library, elibrary databases were used to identify studies that characterized the current view on the problem of choosing the optimal postoperative treatment for colon cancer.Results. the review showed the results of international studies of colon cancer subtypes based on complex multomics characteristics. Particular attention was paid to the description of modern studies on the search for prognostic markers for colon cancer. The relevance of the study of immunohistochemical markers was confirmed by the analysis of the world literature. the outcomes will make it possible to classify colon cancer into molecular subtypes in real clinical practice and, as a consequence, significantly improve the effectiveness of adjuvant therapy.